Kegagalan Kepastian: Membingkai Ulang Manajemen Strategis Melalui Kompleksitas - Hoffni, Brian (Jurnal Manajemen dan Usahawan Indonesia, 2025)
This paper explores the integration of complexity theory into the field of strategic management, arguing that traditional, positivist-based models—such as the planning school, positioning school, and resource-based view—are increasingly inadequate for addressing the volatility, uncertainty, complexity, and ambiguity (VUCA) of contemporary business environments. While classical theories emphasize linearity, stability, and top-down control, complexity theory reconceptualizes organizations as complex adaptive systems (CAS) characterized by emergence, nonlinearity, and continuous learning. Drawing on insights from both historical and contemporary strategic paradigms, this study proposes that complexity theory does not replace but rather extends classical frameworks by enabling more adaptive, iterative, and resilient approaches to strategy. The paper reviews the theoretical foundations of complexity theory, its implications for adaptive strategy, and its application in real-world contexts such as digital transformation, platform ecosystems, and crisis management. It also addresses the challenges of operationalizing complexity theory and calls for a paradigm shift toward more pragmatic, learning-centered models in both research and practice. Ultimately, embracing complexity enables strategic management to better reflect and respond to the dynamic realities of the modern business landscape.